Amorphous zirconia dental restorative material and method of making
By using a method to prepare a composite material of amorphous zirconia matrix and in-situ crystalline particles, the problem of mismatch between dental zirconia ceramics and human tooth enamel was solved, achieving a match between the mechanical and tribological properties of the material, which has good wear resistance and is easy to mass-produce.
Patent Information
- Application Number
- CN202511299670.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-09-12
AI Technical Summary
Existing dental zirconia ceramic materials are mismatched with human tooth enamel in terms of mechanical and tribological properties, resulting in strong abrasiveness to natural teeth. Furthermore, traditional improvement methods suffer from high complexity, high cost, or poor structural controllability.
A composite material consisting of an amorphous zirconia matrix and in-situ crystallized zirconia microcrystalline particles is used. Through low-temperature direct precipitation combined with gradient dehydration and controlled sintering, the material's stiffness and hardness are precisely matched with those of human tooth enamel. Furthermore, the material is firmly bonded through Zr-O-Zr covalent bonds and oxygen vacancy-mediated ionic bonds, thus preventing interfacial failure.
The prepared amorphous zirconia dental restorative material is close to human tooth enamel in terms of hardness, stiffness and wear resistance, avoiding interface failure. The process is simple and controllable and easy to scale up.
Smart Images

Figure CN120788921B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of ceramic oral restoration, in particular to a kind of amorphous zirconia dental restoration material and preparation method thereof. BACKGROUND
[0002] Oral restoration is an implantable medical device used to repair the defect or loss of natural teeth, and its core function is to reconstruct the anatomical shape and physiological function of teeth to restore the masticatory ability, facial aesthetics and quality of life of patients. Zirconia ceramic has become one of the main materials in the field of dental restoration due to its excellent wear resistance, biocompatibility and aesthetics. However, traditional polycrystalline zirconia ceramic is prone to excessive wear of the opposite natural teeth, and even causes iatrogenic damage such as root fracture and occlusal system trauma due to its high hardness, high stiffness and high wear resistance. Therefore, it is of great clinical significance to develop a dental restoration material with mechanical and tribological properties closer to human enamel.
[0003] Currently, the main methods to reduce the mechanical and tribological properties of dental ceramic include infiltrating resin polymer into porous ceramic framework or adjusting mechanical properties through composite material design. For example, patents CN116023066A and CN108578250A reduce the abrasiveness of the material by infiltrating resin into the porous ceramic framework, but introduce problems such as resin aging, staining and bacterial adsorption, and the wear resistance and strength of the material are significantly reduced, making it difficult to meet long-term clinical needs. In addition, patents CN116553938A and CN108743405A attempt to optimize material properties through biomimetic structure design (such as directional porous framework or lamellar structure), but these methods have problems such as high complexity, high cost or poor structure controllability in the preparation process, which limits their large-scale application.
[0004] Therefore, the present application is proposed. SUMMARY
[0005] The present application aims to provide an amorphous zirconia dental restoration material and a preparation method thereof to solve the problem of mismatch between the mechanical and tribological properties of existing dental zirconia ceramic and human enamel, and strong abrasiveness to natural human teeth.
[0006] Firstly, the present application provides an amorphous zirconia dental restoration material, which includes an amorphous zirconia matrix and in-situ crystallized zirconia microcrystalline particles, wherein the content of 90 vol% amorphous zirconia matrix is > 50 vol%, and the content of 50 vol% in-situ crystallized zirconia microcrystalline particles is > 10 vol%. Based on the mixing law of composite materials, within this content range, the low stiffness and low hardness of amorphous zirconia and the high stiffness and high hardness of zirconia microcrystals synergistically act to achieve precise matching of the stiffness, hardness and wear resistance of the material with human enamel.
[0007] As an optional implementation, the hardness of the amorphous zirconia dental restoration material is 3.5-6.0 GPa, and the elastic modulus is 50-100 GPa.
[0008] Secondly, the embodiment of the present application also provides a preparation method of the amorphous zirconia dental restoration material, which realizes in-situ controllable crystallization in the amorphous zirconia matrix through low-temperature direct precipitation combined with gradient dehydration and controlled sintering. The amorphous matrix and the microcrystals are firmly combined through Zr-O-Zr covalent bonds and oxygen vacancy-mediated ionic bonds, which is beneficial to stress transmission between the two phases and avoids interface failure. The specific steps are as follows:
[0009] S1: weigh zirconyl nitrate and dissolve it in water to obtain a zirconium source solution;
[0010] S2: control the temperature of the zirconium source solution to be 6-10 ℃, adjust the pH value of the zirconium source solution to be >7.0, and obtain a zirconia precursor after stirring and aging;
[0011] S3: the zirconia precursor is sequentially washed, molded and dehydrated to obtain a zirconia dry embryo;
[0012] S4: the zirconia dry embryo is sintered to obtain an amorphous zirconia dental restoration material.
[0013] As an optional implementation, the concentration of the zirconium source solution is 2.0-12.0 wt%, and a too low concentration will lead to a too high water content in the precursor, and defects such as pores and cracks in the material during dehydration and sintering, and a too high concentration will cause the precipitation of zirconyl nitrate in the solution.
[0014] As an optional implementation, in S2, the temperature of the zirconium source solution is controlled to be 6-10 ℃, which includes placing the zirconium source solution in an ice bath to control the solution temperature to be 6-10 ℃.
[0015] As an optional implementation, in S2, the pH value of the zirconium source solution is adjusted to be >7.0, which includes using 1-3 mol / L sodium hydroxide solution for pH adjustment.
[0016] As an optional implementation, in S3, the dehydration includes gradiently reducing the humidity in a constant-temperature and constant-humidity box to avoid embryo cracking, first drying at a temperature of 40-80 ℃ and a humidity of 70-90 %RH for 2-4 h;
[0017] then reducing the humidity to 60-80 %RH and drying for 2-4 h;
[0018] and finally reducing the humidity to 30-70 %RH and drying for 16-24 h.
[0019] As an optional implementation, the sintering in S4 further comprises cold isostatic pressing treatment on the zirconia dry compact to improve the dry compact density, and the pressure of the cold isostatic pressing treatment is 300-500 MPa, and the pressure maintaining time is less than 15 min.
[0020] As an optional implementation, the sintering in S4 comprises first heating to 300-500 ℃, and maintaining for 1-3 h, and then cooling to 200-300 ℃ and cooling with the furnace, wherein the heating and cooling rates are both 2-10 ℃ / min.
[0021] Compared with the prior art, the embodiments of the present application have the following advantages and beneficial effects:
[0022] 1. The embodiments of the present application provide a novel amorphous zirconia dental restoration material, which uses amorphous zirconia with low hardness and rigidity as a material matrix, and accurately controls the in-situ crystallization zirconia microcrystal content, and based on the composite material mixing law, in the microcrystal content range of the prepared material, the low rigidity and low hardness of the amorphous zirconia and the high rigidity and high hardness of the zirconia microcrystals are synergistically combined to realize that the mechanical and tribological properties of the material are close to human tooth enamel, and the material has great application prospects in the field of dental restoration materials.
[0023] 2. The embodiments of the present application prepare an amorphous zirconia dental restoration material based on a direct precipitation method by adjusting a sintering process. The method can realize in-situ controllable crystallization in the amorphous zirconia matrix, and the amorphous matrix and the microcrystals are firmly combined through Zr-O-Zr covalent bonds and oxygen vacancy-mediated ionic bonds, which is beneficial to stress transmission between the two phases and avoids interface failure. In addition, the provided material preparation process is simple and controllable, the required equipment is common in the field, the raw materials used are inexpensive, non-toxic and non-polluting, and easy to mass produce. BRIEF DESCRIPTION OF DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiments. It should be understood that the following drawings only show some embodiments of the present application, and therefore should not be considered as a limitation on the scope, and for those skilled in the art, other related drawings can also be obtained without creative labor. In the drawings:
[0025] Figure 1 An optical photo of the amorphous zirconia dental restoration material prepared in Embodiment 1 of the present application;
[0026] Figure 2A scanning electron microscope photo of the amorphous zirconia dental restoration material prepared in Example 1 of the present application;
[0027] Figure 3 An energy dispersive X-ray spectrum of the amorphous zirconia dental restoration material prepared in Example 1 of the present application;
[0028] Figure 4 An X-ray diffraction pattern of the amorphous zirconia dental restoration material prepared in Example 1 of the present application;
[0029] Figure 5 The elastic modulus and hardness of the amorphous zirconia dental restoration material prepared in Example 1 of the present application;
[0030] Figure 6 A wear volume diagram of the surface of the amorphous zirconia dental restoration material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application.
[0032] Therefore, the detailed description of the embodiments of the present application provided below is not intended to limit the scope of the claimed present application, but only represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative efforts fall within the scope of protection of the present application.
[0033] In terms of material selection, amorphous zirconia exhibits different mechanical properties from polycrystalline zirconia due to its unique amorphous structure, such as lower hardness and elastic modulus, while maintaining good wear resistance and chemical stability. However, there are few studies on the application of amorphous zirconia in dental restoration, especially in terms of how to control its mechanical and tribological properties through preparation process. Therefore, it is of great scientific value and clinical application prospect to develop an amorphous zirconia dental restoration material that matches the mechanical and tribological properties of human enamel by optimizing its preparation process and reducing the abrasiveness to natural teeth.
[0034] The problem of high abrasiveness of polycrystalline zirconia ceramic to natural teeth has not been solved in the prior art, and the design of resin infiltration or composite material introduces new performance defects. Therefore, the present application provides a preparation method of an amorphous zirconia dental restoration material, which comprises the following contents:
[0035] Step 1: Zirconium source solution preparation: weigh zirconyl nitrate and dissolve it in deionized water, fully stir using a magnetic stirrer, stirring time is 20-40 min, stirring speed is 200-800 rpm, obtain zirconium source solution, zirconium source solution has zirconyl nitrate content of 2.0-12.0 wt%.
[0036] Step 2: Precursor preparation: place the zirconium source solution in an ice bath, control the solution temperature to keep at 6-10 ℃, stir the zirconium source solution and adjust the solution pH value > 7.0 using sodium hydroxide solution with concentration of 1-3 mol / L, continue to stir for 20-40 min, then stop stirring and age for 3-8 h, obtain zirconia precursor.
[0037] Step 3: Embryo preparation: wash and filter the zirconia precursor repeatedly for 3-6 times using deionized water; inject the precursor into a centrifuge tube, use a centrifuge to separate the excess water in the precursor, centrifugal speed is 6000-15000 rpm, centrifugal time is 10-30 min, obtain zirconia wet embryo; dry the wet embryo in a constant temperature and humidity box, specifically first dry at 40-80 ℃ and 70-90 %RH for 2-4 h, then reduce the humidity to 60-80 %RH and dry for 2-4 h, finally reduce the humidity to 30-70 %RH and dry for 16-24 h, obtain zirconia dry embryo.
[0038] Step 4: Sintering treatment: perform cold isostatic pressing treatment on the zirconia dry embryo, the cold isostatic pressing treatment is performed at a pressure of 300-500 MPa, pressure holding time < 15 min; then place it in a sintering furnace, first heat to 300-500 ℃, keep for 1-3 h, then cool to 200-300 ℃ and cool with the furnace, obtain amorphous zirconia dental restoration material, wherein the heating rate and the cooling rate are both 2-10 ℃ / min.
[0039] Example 1: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which includes the following contents:
[0040] Step 1: Zirconium source solution preparation: weigh zirconyl nitrate and dissolve it in deionized water, fully stir using a magnetic stirrer, stirring time is 30 min, stirring speed is 500 rpm, obtain zirconium source solution, zirconium source solution has zirconyl nitrate content of 5 wt%.
[0041] Step 2: Precursor preparation: place the zirconium source solution in an ice bath, control the solution temperature to keep at 8 ℃, stir the zirconium source solution and adjust the solution pH value to 8.0 using sodium hydroxide solution with concentration of 2 mol / L, continue to stir for 30 min, then stop stirring and age for 5 h, obtain zirconia precursor.
[0042] Step 3: Embryo preparation: The zirconium oxide precursor was repeatedly washed and filtered with deionized water for 5 times; 3 ml of the precursor was taken and injected into a 5 ml centrifuge tube, and the centrifuge was used to separate the excess water in the precursor, with a centrifugal speed of 10000 rpm and a centrifugal time of 15 min, to obtain a zirconium oxide wet embryo; the wet embryo was dried in a constant temperature and humidity box, specifically first at a temperature of 70 ℃ and a humidity of 80 %RH for 3 h, then the humidity was reduced to 70 %RH for 3 h, and finally the humidity was reduced to 50 %RH for 20 h, to obtain a zirconium oxide dry embryo.
[0043] Step 4: Sintering treatment: the zirconium oxide dry embryo was subjected to cold isostatic pressing treatment, which was carried out at a pressure of 450 MPa for 10 min; then it was placed in a sintering furnace, first heated to 450 ℃ and kept for 2 h, then cooled to 250 ℃ and cooled with the furnace, to obtain an amorphous zirconia dental restoration material, wherein the heating rate and the cooling rate were both 5 ℃ / min.
[0044] Example 2: The present application provides a preparation method of an amorphous zirconia dental restoration material, which includes the following contents:
[0045] Step 1: Preparation of zirconium source solution: zirconyl nitrate was weighed and dissolved in deionized water, and a magnetic stirrer was used for sufficient stirring, with a stirring time of 20 min and a stirring speed of 800 rpm, to obtain a zirconium source solution, and the zirconium source solution had a zirconyl nitrate content of 2.0 wt%.
[0046] Step 2: Preparation of precursor: the zirconium source solution was placed in an ice bath, and the solution temperature was controlled to be kept at 6 ℃; the zirconium source solution was stirred and the pH value of the solution was adjusted to 9.0 by using a sodium hydroxide solution with a concentration of 1 mol / L; the stirring was continued for 20 min, then the stirring was stopped and the solution was aged for 3 h, to obtain a zirconium oxide precursor.
[0047] Step 3: Embryo preparation: The zirconium oxide precursor was repeatedly washed and filtered with deionized water for 3 times; 3 ml of the precursor was taken and injected into a 5 ml centrifuge tube, and the centrifuge was used to separate the excess water in the precursor, with a centrifugal speed of 6000 rpm and a centrifugal time of 10 min, to obtain a zirconium oxide wet embryo; the wet embryo was dried in a constant temperature and humidity box, specifically first at a temperature of 40 ℃ and a humidity of 70 %RH for 2 h, then the humidity was reduced to 60 %RH for 2 h, and finally the humidity was reduced to 30 %RH for 16 h, to obtain a zirconium oxide dry embryo.
[0048] Step 4: sintering treatment: the zirconia green body is subjected to cold isostatic pressing treatment, the cold isostatic pressing treatment is performed at a pressure of 300 MPa, the pressure holding time is 9 min; then it is placed in a sintering furnace, first heated to 500 ℃, and held for 1 h, then cooled to 200 ℃ and cooled with the furnace, to obtain an amorphous zirconia dental restoration material, wherein the heating rate and the cooling rate are both 2 ℃ / min.
[0049] Example 3: The example of the present application provides a preparation method of an amorphous zirconia dental restoration material, which includes the following contents:
[0050] Step 1: zirconium source solution preparation: zirconyl nitrate is weighed and dissolved in deionized water, a magnetic stirrer is used for sufficient stirring, the stirring time is 40 min, and the stirring speed is 200 rpm, to obtain a zirconium source solution, the zirconium source solution has a zirconyl nitrate content of 12.0 wt%.
[0051] Step 2: precursor preparation: the zirconium source solution is placed in an ice bath, the solution temperature is controlled to be kept at 10 ℃, the zirconium source solution is stirred and the pH value of the solution is adjusted to be 9.0 by using a sodium hydroxide solution with a concentration of 3 mol / L, the stirring is continued for 40 min, then the stirring is stopped and the solution is aged for 8 h, to obtain a zirconia precursor.
[0052] Step 3: green body preparation: the zirconia precursor is repeatedly washed and filtered with deionized water for 6 times; 3 ml of the precursor is measured and injected into a 5 ml centrifuge tube, the centrifuge is used to separate the excess water in the precursor, the centrifugal speed is 15000 rpm, and the centrifugal time is 30 min, to obtain a zirconia wet green body; the wet green body is dried in a constant temperature and humidity box, specifically first at a temperature of 80 ℃ and a humidity of 90 %RH for 4 h, then the humidity is reduced to 80 %RH for 4 h, and finally the humidity is reduced to 70 %RH for 24 h, to obtain a zirconia dry green body.
[0053] Step 4: sintering treatment: the zirconia green body is subjected to cold isostatic pressing treatment, the cold isostatic pressing treatment is performed at a pressure of 500 MPa, the pressure holding time is 8 min; then it is placed in a sintering furnace, first heated to 300 ℃, and held for 3 h, then cooled to 300 ℃ and cooled with the furnace, to obtain an amorphous zirconia dental restoration material, wherein the heating rate and the cooling rate are both 10 ℃ / min.
[0054] Example 4: The example of the present application provides a preparation method of an amorphous zirconia dental restoration material, which is different from example 1 in that the zirconium source solution has a zirconyl nitrate content of 1.5 wt%, and the other steps remain unchanged.
[0055] Example 5: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that the content of zirconium oxide nitrate in the zirconium source solution is 13 wt%, and the remaining steps remain unchanged.
[0056] Example 6: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that the zirconium source solution is placed in an ice bath to control the solution temperature to keep at 5 ℃, and the remaining steps remain unchanged.
[0057] Example 7: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that the zirconium source solution is placed in an ice bath to control the solution temperature to keep at 11 ℃, and the remaining steps remain unchanged.
[0058] Example 8: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that the zirconium source solution is stirred and the pH value of the solution is adjusted to 7.0 by using a sodium hydroxide solution with a concentration of 2 mol / L, and the remaining steps remain unchanged.
[0059] Example 9: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that cold isostatic pressing is not performed in step 4, and the remaining steps remain unchanged.
[0060] Example 10: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that the zirconia dry embryo is obtained by directly drying for 26 h in an environment with a temperature of 70 ℃ and a humidity of 50 %RH in a constant temperature and humidity box without gradient drying in step 3, and the remaining steps remain unchanged.
[0061] Example 11: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that the temperature is first raised to 550 ℃ and kept for 2 h in step 4, and the remaining steps remain unchanged.
[0062] Example 12: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that the temperature is first raised to 280 ℃ and kept for 2 h in step 4, and the remaining steps remain unchanged.
[0063] Example 13: The example of the present application provides a preparation method of amorphous zirconia dental restoration material, which is different from example 1 in that the temperature is not lowered to 250 ℃ at a rate of 5 ℃ / min in step 4, but is raised to 450 ℃ and kept for 2 h before being directly cooled with the furnace, and the remaining steps remain unchanged.
[0064] Performance test
[0065] The repair materials prepared in Examples 1-13 were subjected to the following performance tests:
[0066] 1) Elastic modulus and hardness test: The elastic modulus and hardness of the amorphous zirconia dental repair material were tested using a G200 nanomechanical testing system (Keysight, USA), a Berkovich diamond indenter with a curvature radius of 20 nm was selected for the test, and the maximum indentation load was 20 mN.
[0067] 2) Unidirectional scratch friction and wear test: The tribological properties of the amorphous zirconia dental repair material were tested using a G200 nanomechanical testing system (Keysight, USA), a Conical diamond indenter with a curvature radius of 10 μm was selected for the test, and the normal load was 10 mN.
[0068] 3) Repair material composition test: The chemical composition of the amorphous zirconia dental repair material was tested using an X'pert pro-MPD X-ray diffractometer (PANalytical, Netherlands), a Cu Kα radiation source was used for the test, the voltage was 40 kV, the current was 30 mA, the 2θ scanning range was 10°-90°, the step size was 0.02°, and a pure amorphous zirconia reference spectrum was obtained under the same parameters. By introducing a crystal phase structure model into the Rietveld refinement and fitting the amorphous part as an independent phase, the crystal and amorphous phase contents were calculated.
[0069] The test results are shown in Table 1 below:
[0070] Table 1
[0071]
[0072] The optical photograph of the amorphous zirconia dental repair material prepared in Example 1 is shown in Figure 1 , the scanning electron microscope photograph is shown in Figure 2 , and it can be seen from Figure 1 and Figure 2 that the amorphous zirconia dental repair material is translucent and milky white, and the structure is uniform and dense. The energy dispersive X-ray spectrum and X-ray diffraction spectrum of the amorphous zirconia dental repair material prepared in Example 1 are shown in Figure 3 and Figure 4 , and it can be seen from Figure 3 and Figure 4 that the amorphous zirconia dental repair material is composed of an amorphous zirconia matrix and a small amount of in-situ crystallized zirconia microcrystalline particles, and the contents of the amorphous zirconia matrix and the zirconia microcrystalline particles are 75% and 25%, respectively, and Figure 5It can be seen that the elastic modulus of the amorphous zirconia dental restoration material prepared in Example 1 is 84 GPa, the hardness is 4.5 GPa, and the wear volume is close to that of human tooth enamel. It can be seen that the amorphous zirconia dental restoration material prepared in the embodiment has beautiful color and appearance, and the mechanical properties and wear resistance are significantly lower than those of commercial dental ceramics, and are close to those of human tooth enamel. Figure 6 It can be seen that the wear volumes of the amorphous zirconia dental restoration material and the surface of human tooth enamel are 2.64 μm 3 and 2.44 μm 3 , respectively, and there is no significant difference.
[0073] According to Table 1, it can be seen from the comparison of Examples 1-3 and Example 4 that when the content of zirconium oxide nitrate in the zirconium source solution is less than 2 wt%, the water content of the prepared precursor is too high, which causes defects such as pores and cracks in the material during dehydration and sintering, and the material is broken; it can be seen from the comparison of Examples 1-3 and Example 5 that when the content of zirconium oxide nitrate in the zirconium source solution is greater than 12 wt%, zirconium oxide nitrate in the solution will precipitate, resulting in a large amount of impurities, so the content of zirconium oxide nitrate in the zirconium source solution is preferably 2.0-12.0 wt%.
[0074] It can be seen from the comparison of Examples 1-3 and Example 6 that when the ice bath temperature control is less than 6 ℃, the zirconia precursor cannot be precipitated; it can be seen from the comparison of Examples 1-3 and Example 7 that when the ice bath temperature control is greater than 10 ℃, the precursor cannot be precipitated, so the ice bath temperature control is preferably 6-10 ℃.
[0075] It can be seen from the comparison of Examples 1-3 and Example 8 that when the pH value of the solution adjusted by the sodium hydroxide solution is not alkaline, the zirconia precursor cannot be precipitated, so the pH value of the solution adjusted by the sodium hydroxide solution is preferably greater than 7.0.
[0076] It can be seen from the comparison of Examples 1-3 and Example 9 that when the zirconia dry embryo is not subjected to cold isostatic pressing treatment and is directly sintered, the material contains a large number of defects such as pores and cracks, and has low density, so it is more appropriate to take cold isostatic pressing treatment.
[0077] It can be seen from the comparison of Examples 1-3 and Example 10 that if the drying process of the zirconia dry embryo is not subjected to gradient drying, the embryo will dehydrate and shrink too fast, the material will have defects such as pores and cracks, and will be broken, so it is more appropriate to take gradient drying.
[0078] It can be seen from the comparison of Examples 1-3 and Example 11 that when the sintering temperature is higher than 500℃, excessive crystallization is caused, resulting in too high content of zirconia crystal particles with high hardness and rigidity in the material, and the overall hardness, rigidity and wear resistance of the material are much higher than human tooth enamel; it can be seen from the comparison of Examples 1-3 and Example 12 that when the sintering temperature is lower than 300℃, in-situ crystallization of zirconia is inhibited, resulting in too low overall mechanical properties and wear resistance of the material, therefore, it is more appropriate when the sintering temperature is 300-500℃. It can be seen from the comparison of Examples 1-3 and Example 13 that when the body is directly cooled in the furnace after sintering, the cooling shrinkage speed of the body is too fast, and the material is broken, therefore, it is more appropriate to cool the body to 200-300℃ and then cool it in the furnace after sintering.
[0079] The above detailed description of the specific embodiments has further detailed the purposes, technical solutions and beneficial effects of the present application, and it should be understood that the above description is only a specific embodiment of the present application and is not used to limit the protection scope of the present application, and any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. An amorphous zirconia dental restorative material, characterized in that, The amorphous zirconia dental restoration material comprises an amorphous zirconia matrix and in-situ crystallized zirconia microcrystalline particles, wherein the content of the amorphous zirconia matrix is 90 vol%>50 vol%, and the content of the in-situ crystallized zirconia microcrystalline particles is 50 vol%>10 vol%. The preparation method of the amorphous zirconia dental restoration material comprises the following steps: S1: weighing zirconyl nitrate and dissolving it in water to obtain a zirconium source solution, wherein the concentration of the zirconium source solution is 2.0-12.0 wt%; S2: controlling the temperature of the zirconium source solution to be 6-10 ℃ and adjusting the pH value of the zirconium source solution to be greater than 7.0, and then stirring and aging to obtain a zirconia precursor; S3: sequentially performing washing, injection molding and dehydration on the zirconia precursor to obtain a zirconia dry embryo; S4: sintering the zirconia dry embryo to obtain the amorphous zirconia dental restoration material, and before the sintering, the zirconia dry embryo is further subjected to cold isostatic pressing treatment; The dehydration in S3 comprises the following steps: first, drying for 2-4 h in a constant temperature and humidity box at a temperature of 40-80 ℃ and a humidity of 70-90 %RH; then, reducing the humidity to 60-80 %RH and drying for 2-4 h; finally, reducing the humidity to 30-70 %RH and drying for 16-24 h. The sintering in S4 comprises the following steps: first, heating to 300-500 ℃ and holding for 1-3 h; then, cooling to 200-300 ℃ and cooling with the furnace.
2. The amorphous zirconia dental restorative material according to claim 1, characterized in that The hardness of the amorphous zirconia dental restoration material is 3.5-6.0 GPa, and the elastic modulus is 50-100 GPa.
3. A method of producing an amorphous zirconia dental restorative material as claimed in claim 1 or 2, characterized in that, The preparation method of the amorphous zirconia dental restoration material comprises the following steps: S1: weighing zirconyl nitrate and dissolving it in water to obtain a zirconium source solution, wherein the concentration of the zirconium source solution is 2.0-12.0 wt%; S2: controlling the temperature of the zirconium source solution to be 6-10 ℃ and adjusting the pH value of the zirconium source solution to be greater than 7.0, and then stirring and aging to obtain a zirconia precursor; S3: sequentially performing washing, injection molding and dehydration on the zirconia precursor to obtain a zirconia dry embryo; S4: sintering the zirconia dry embryo to obtain the amorphous zirconia dental restoration material, and before the sintering, the zirconia dry embryo is further subjected to cold isostatic pressing treatment; The dehydration in S3 comprises the following steps: first, drying for 2-4 h in a constant temperature and humidity box at a temperature of 40-80 ℃ and a humidity of 70-90 %RH; then, reducing the humidity to 60-80 %RH and drying for 2-4 h; finally, reducing the humidity to 30-70 %RH and drying for 16-24 h. The sintering in S4 comprises the following steps: first, heating to 300-500 ℃ and holding for 1-3 h; then, cooling to 200-300 ℃ and cooling with the furnace.
4. The method for preparing an amorphous zirconia dental restorative material according to claim 3, characterized in that, The control of the temperature of the zirconium source solution in S2 comprises the following steps: placing the zirconium source solution in an ice bath and controlling the temperature of the solution to be 6-10 ℃.
5. The method for preparing an amorphous zirconia dental restorative material according to claim 3, characterized in that, The adjustment of the pH value of the zirconium source solution in S2 comprises the following steps: adjusting the pH value by using 1-3 mol / L sodium hydroxide solution.
6. The method for preparing an amorphous zirconia dental restorative material according to claim 3, characterized in that, The pressure of the cold isostatic pressing treatment is 300-500 MPa, and the pressure holding time is less than 15 min.
7. The method for preparing an amorphous zirconia dental restorative material according to claim 3, characterized in that, The rate of the temperature increase and the temperature decrease is 2 to 10 ℃ / min. The rate of the temperature increase and the temperature decrease is 2 to 10 ℃ / min.
Citation Information
Patent Citations
Resin permeated silicate composite material as well as preparation and application thereof
CN108578250A
Zirconium oxide / resin bionic composite material for denture and preparation method thereof
CN108743405A
Resin permeable ceramic and preparation method thereof
CN116023066A
Porous ceramic skeleton, preparation method thereof and double-bionic resin ceramic composite material
CN116553938A
Zirconia ceramic material applied to dental restoration and preparation method of zirconia ceramic material
CN103550069A